2018
DOI: 10.1002/cam4.1688
|View full text |Cite
|
Sign up to set email alerts
|

Effect of marital status on survival in glioblastoma multiforme by demographics, education, economic factors, and insurance status

Abstract: The relationship between marital status and glioblastoma multiforme (GBM) has not been addressed in depth. Here, we aimed to investigate the association between marital status and survival in GBM. We searched the Surveillance, Epidemiology, and End Results (SEER) database and extracted the data of eligible patients diagnosed with GBM after 2004. Marital status was classified as married, divorced/separated, widowed, and single. A Kaplan‐Meier test was conducted to compare the survival curves of different groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 35 publications
1
41
0
Order By: Relevance
“…It is the first time shown that insurance was an independent prognostic factor and was incorporated to newly prognostic nomogram for STS patients with surgery. Uninsured status would lead to decreased diagnosis rates and increased conservative treatment for cancers,26 thus undermine patients’ prognosis. Nowadays, the treatment for STS has become multidisciplinary and expensive.…”
Section: Discussionmentioning
confidence: 99%
“…It is the first time shown that insurance was an independent prognostic factor and was incorporated to newly prognostic nomogram for STS patients with surgery. Uninsured status would lead to decreased diagnosis rates and increased conservative treatment for cancers,26 thus undermine patients’ prognosis. Nowadays, the treatment for STS has become multidisciplinary and expensive.…”
Section: Discussionmentioning
confidence: 99%
“…Marriage is one of the most important source of social support, which affects physical health through integrative physiological mechanisms [6]. Previous studies have pointed out that married patients tend to have better survival outcome in several cancer types [7][8][9][10][11][12][13][14][15]. However, whether marriage has a "protective" effect for G-NEN patients has not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…These results parallel the findings of Arnold et al (2008), who found individuals with college-level education to be much less likely than those with no college education to have anxiety, depression or both. A possible explanation could be that the PBT with higher education levels are more aware of their psychological and physical needs and are therefore able to care more for their health and willing to receive more effective interventions early on (Xie, Yang, Liu, & Zhao, 2018;Hussain et al, 2008). However, the education level may influence affective disorders through income.…”
Section: Level Of Educationmentioning
confidence: 99%